The Prisoner - Brown, Alice (Saga Egmont, 2023)
Homecoming hero Jeffrey Blake returns after a stint in prison and tries to embed himself back into his former life. Blake hopes to reconcile with his wife and find his place back in his family alongside his aging father but is met with obstacles and judgement, as well as trying to solve the mystery of a stolen necklace in the family with his wife as the prime suspect. Alice Brown is an American novelist and short-story writer. She is best known for her tales about New England and as a writer of stories with local colour. Born in New Hampshire in 1857, Brown\'s stories often portray a female protagonist in a domestic setting. Her first novel, \'Stratford-by-the-Sea\', was published in 1884. It cemented Brown as part of the Boston literary scene, but by the time she died in 1948 (aged 91), many of her stories had been forgotten about and were no longer in print.